Cultivating Good Practices of In-Depth Learning by High School Teachers in Makassar City: a Qualitative Case Study Analysis - Alwi, Alimin (Unika Santu Paulus Ruteng, 2026)
This study aims to describe and analyze good practices in the implementation of Deep Learning among high school teachers participating in the Makassar City Class 1K Batch 1 Program, particularly in relation to the context of implementation, supporting factors, obstacles, and good practices that emerged in the learning process. This research was motivated by the education transformation program initiated by the Ministry of Primary and Secondary Education (Kemendikdasmen) through the South Sulawesi Province Teacher and Education Personnel Center, which promotes a learning paradigm oriented towards awareness, meaningfulness, and joy of learning. The research used a qualitative approach with a case study design and involved 33 teachers from 11 public and private schools. Data collection techniques included observation, interviews, and documentation, which were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that deep learning is able to facilitate active student engagement through reflective discussions, problem solving, and collaborative activities. Teachers develop comprehensive lesson plans in the form of teaching modules that are aligned with learning objectives and outcomes. However, the implementation of learning faces obstacles in the form of time constraints, low student interest in reading, a learning orientation that is still focused on grades, diversity in initial abilities, and limitations in learning media. Nevertheless, there are good practices that show an increase in motivation, enthusiasm, and meaningful learning experiences for students. This study concludes that deep learning has significant potential to improve the quality of the teaching and learning process, but requires more systematic support through the strengthening of academic culture, the provision of learning facilities, and the continuous professional development of teachers. These findings can be used as a reference for policy makers and educational institutions in developing a more extensive and sustainable deep learning-based teacher training model.